Analisis Tax Planning sebagai Alternatif Efisiensi Pajak Pertambahan Nilai pada PT. ABC (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Companies generally assume that paying taxes is a burden that can directly reduce the amount of net profit earned. This view is not entirely wrong because taxes are indeed an obligation that must be paid by companies to the state and are recorded as a deduction in financial statements. However, it is important to understand that taxes are not merely a burden, but also contribute to national development. In the context of taxation in Indonesia, companies are taxpayers who are required to fulfill their tax obligations in accordance with applicable regulations, one of which is the obligation to pay Value Added Tax (VAT) on the delivery of Taxable Goods (BKP) and/or Taxable Services (JKP). VAT is an indirect tax charged to the end consumer, but in practice, taxable entrepreneurs (PKP) are obliged to collect, deposit, and report the VAT. Therefore, efficiency in VAT management is crucial to avoid excess burdens that should be minimized legally through tax planning strategies. Tax planning is the first step that companies can take to minimize their tax burden without violating applicable tax regulations. One strategy that can be implemented in VAT tax planning is Input Tax optimization, namely by ensuring that every BKP/JKP purchase transaction made with fellow PKP allows the company to credit the maximum Input Tax. PT ABC is a company that experiences fluctuations in the amount of VAT payable from month to month. This indicates that the company is not yet fully efficient in managing creditable Input Tax. This issue needs to be addressed seriously because this inefficiency has the potential to increase the amount of VAT that must be paid, which ultimately impacts the company's profitability.